(untitled) (Plant Tissue Culture and Biotechnology, 2009)
The genetic diversity of 18 jute genotypes of the two cultivated species Corchorus capsularis L. and C. olitorius L. which include released varieties and collected races, referred to as accessions was evaluated. DNA profiling was generated using sequence independent RAPD markers. A total of 140 scorable loci were observed and a dendrogram was constructed with these markers. The relationship that is portrayed by this clustering also agreed with the available pedigree information on jute. Two major clusters representing the two species were resolved among the genotypes that were examined in the study. This genetic distance information could be useful in breeding programs in order to introduce agronomically important traits such as short field duration, low temperature tolerance, snow white fibre, higher harvest index etc. From the study one C. olitorius and two C. capsularis varieties were found more suitable for their selection as seed parent against different accessions for improvement because of their higher genetic distant relationship within species. However, more extensive molecular data are needed in order to reach a general conclusion about the relationship between jute genotypes. Key words: Jute, Polymorphism, Genetic diversity, RAPD D.O.I. 10.3329/ptcb.v17i2.3239 Plant Tissue Cult. & Biotech. 17(2): 183-191, 2007 (December)